The Effect Of Entrepreneurial Orientation On Marketing Performance Of Street Food MSMEs In Pontianak City With Product Innovation as a Mediation - Andrean; Lie Heng (Economos : Jurnal Ekonomi dan Bisnis, 2025)
This study investigates the impact of entrepreneurial orientation on the marketing performance of Street Food MSMEs with product innovation as an intermediary. This study uses a quantitative method with an associative approach. Data were collected from 140 street food MSMEs from a population of 245 businesses selected using a purposive sampling technique, with the criteria of having been operating for at least three years and having a fixed/semi-fixed location. Data analysis used Structural Equation Modeling (SEM) with AMOS software. The results showed that entrepreneurial orientation had a significant positive effect on product innovation (0.531; p